Aplikasi Plant Growth Promoting Rhizobacteria (PGPR) dan Limbah Air Kolam Lele dengan Sistem Irigasi Tetes terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - PUTRA, I GEDE KRISNA PRATAMA; RAI, I NYOMAN; WIJANA, GEDE (Agrotrop : Journal on Agriculture Science, 2022)
The Application of Plant Growth Promoting Rhizobacteria (PGPR) and the Waste of Catfish Tank Water with Drip Irrigation System towards the Growth and the Yield of Pakcoy ( Brassica rapa L . ). Pakcoy ( Brassica rapa L . ) is a leaf vegetable commodity belonging to the Brassicaceae family. The productivity of the mustard plant has fluctuated in recent years. To handle that, it is necessary to innovate the treatment techniques in the cultivation of pakcoy. The application of PGPR and waste of catfish tank water using a drip irrigation system is one solution to improve the quality and production of pakcoy. This research aims to find the best dose of PGPR when combined with the waste of catfish tank water. This research used a split-plot randomized block design with 2 factors. The first factor was a resource of irrigation water which consists of 2 treatments level, namely the irrigation without the waste of catfish tank water and irrigation with the waste of catfish tank water. Meanwhile, the second factor was the dose of PGPR which consists of 5 treatments level, i.e. PGPR dose of 0, 100, 200, 300, and 400 ml/plant. The results showed that the application of PGPR at a dose of 200 ml/plant was able to provide better growth and yield of pakcoy than the other PGPR doses. This can be seen from the fresh weight of the pakcoy crown, which is 42.64 g. Furthermore, the factor of irrigation water sources with the waste of catfish tank water provided the highest yield of pakcoy for all observation variables. The interaction of PGPR dose of 200 ml/plant and waste of catfish tank water gave the highest crown fresh weight of 23.45 g.